A comprehensive exploration of mercury adsorption sites on the carbonaceous surface: A DFT study. (15th December 2020) - Yan, Ge; Gao, Zhengyang; Zhao, Mingliang; Yang, Weijie; Ding, Xunlei
Highlights: Twelve different kinds of defective carbonaceous surfaces were researched systematically. The real adsorption sites of Hg 0 on the unburned carbon in fly ash. The defective carbon surface exceptional adsorption performance. The influence of oxygen functional groups on Hg 0 adsorption. Abstract: Mercury pollution released from coal-fired power plants has caused worldwide concern for its toxicity, global range transportation, and bioaccumulation. Unburned carbon in fly ash is considered to be a promising adsorbent to effectively remove elemental mercury. However, the active sites of the unburned carbon for Hg 0 adsorption have not been clearly identified, which greatly hinders the development of effective adsorbents. To reveal the adsorption sites of the carbonaceous surface, the adsorption process of Hg 0 on different carbonaceous surfaces was systematically investigated through density functional theory. The Mayer bond order, Electron localization function, and Electron density difference were used to analyze the adsorption mechanism of Hg 0 . Meanwhile, the oxygen-containing functional groups were also considered to research the influence on mercury adsorption with the defective surface. The adsorption of Hg 0 on defective carbonaceous surfaces is associated with stable chemisorption, and surface defects can significantly improve the adsorption energy of Hg 0 . This theoretical study provides theoretical guidance for the development of mercury removal technology with carbon materials in the coal-fired power plant.